Jakość życia a percepcja czasu u osób chorych na schizofrenię - Stecka, Mariola (Current Problems of Psychiatry, 2015)
Aim. The subject of the investigation is to explore relations between quality of life (family, social, occupational), and time perception in patients with schizophrenia (N=30). The aim is to improve the quality of life with people suffering from illness.Method. Methods used in investigations are Temporal Orientation Questionnaire AION-2000, devised by C.S. Nosal and B. Bajcar (2004), and socio-demographic survey, which contained three questions about family, social and occupational quality of life. Examinated persons gave answers on Likert’s scale (1 - very bad, 5 - very good).Results. Investigations showed that there are important relations between dimensions of time orientation and family, social, occupational quality of life. Most value results are involved with decrease in family quality of life, and in the same time increase in the perception that the time is destructive, what is more, the increase of the social and family quality of life is connected with concentration on present and future orientation.Conclusions. There are scientifically proved connections between perception of time and level of quality of life in patients with schizophrenia. Focusing on destructive effects of time and concentrating on past, affects on decrease in general quality of life.